SUCCESS AND FAILURE FACTORS OF THE IMPLEMENTATION OF COMPUTER BASED INFORMATION SYSTEMS IN THE GOVERNMENT INSTITUTIONS OF MATARAM CITY: INFORMATION SYSTEM RESOURCE PERSPECTIVE - Budi Santoso; Emilia Septiani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
The purposes of this study were to identify the factors of success and failure of the implementation of computer-based information systems at the Departments of Government in the city of Mataram, and to determine the position or to map the information system, information resources’ perspectives. This research is a descriptive study by collecting primary data from 32 government agencies which was based on interviews based on the questionnaire that has been prepared. The results showed that the persistence of the mismatch of education and skills resource officers from the perspective of human information. Inadequate readiness of the hardware owned by the Government Agencies. Most of operating systems (OS) used and Microsoft Windows-based applications are still vulnerable to a computer virus attacks. SOP is not owned by most of the Government Agencies, and the some have still not complied. The computer networking is still underdeveloped in most of the Government Agencies. Finally, the data or information has not been fully utilized by almost all levels of management to the decision-making process. To that end, it is suggested that it is necessary to strengthen and empowering capabilities and expertise personnel, upgrading and server procurement, the development of wireless-based network for the short term, while maintaining a commitment at all levels of management to utilize the data/ information in the decision-making process